A FRAMEWORK FOR THE CONSERVATION AND VALORISATION OF COLONIAL ARCHITECTURAL HERITAGE OF COASTAL COLONIAL TOWNS, GHANA - Owusu, Emmanuel Banahene; Quagraine, Victor Kwesi (Journal Sampurasun : Interdisciplinary Studies for Cultural Heritage, 2024)
Coastal Colonial Towns (CCTs) of Ghana contain Colonial Architectural Heritage (CAH). The CAH are valuable assets which possess economic and utility values which can be harnessed for development. Over the years, the morphologies of the CCTs have been exposed to destructive forces, putting the CAH at risk. There is the need to rescue the CAH. This study focused on establishing a framework to guide the identification, conservation and valorisation of the CAH, not only to prevent their destruction but most importantly make them socio-economically viable to national developments. The study relied mostly on scholarly literature to first identify the gaps associated with pertinent theories; none of the morphological approaches considers both the micro and macro–Urban Tissues (UT) and both the human and environmental factors at the same time; and the theories have not been explored well in Ghana to enable the identification and conservation of heritage items. The proposed framework which is to fill the gap, is a synthesis of the morphological approaches (Historico-geographic, Process-typological and Space syntax), the Power theory and the Historic Urban Landscape approach. The study makes significant contribution by allowing both the macro and micro UTs as well as the environmental and human factors to be considered for the identification, conservation and valorization of CAH. Moreso, the study produced a framework which can be adapted to conserve and valorise the CAH of the CCTs of Ghana.